HIV prophylaxis: an essential role for T cells and adjuvants in recombinant mucosal Lactobacillus acidophilus vaccines - LeCureux, Jonathan Spicer, author; Dean, Gregg, advisor; Aboellail, Tawfik, committee member; Chen, Chaoping, committee member; Zabel, Mark, committee member (Colorado State University. Libraries, 2016)
Current HIV vaccines have poor efficacy, with inconsistent levels of protection following mucosal HIV exposure. Lactic acid bacteria offer an alternative vaccine vector targeting the primary site of HIV infection, the mucosa. In these studies we evaluated the immunogenicity of several strains of Lactobacillus acidophilus expressing HIV membrane proximal external region (MPER), a portion of HIV envelope that contains broadly neutralizing antibody binding sites. We evaluated MPER-only expressing strains along with strains expressing adjuvants (interleukin-1β or flagellin) to improve immunogenicity against the HIV MPER. We compared the adjuvant strains to the MPER-only strain by oral administration in BALB/c mice to observe these improvements, and in CD40L-/- mice to observe if T cell help was necessary. Some BALB/c animals were also placed on a modified diet supplemented with prebiotic rice bran to observe any influence on vaccine immunogenicity. Resulting antibody responses and interleukin-17 levels were measured by ELISA, and T and B cell levels were measured by flow cytometry. Here we show that the addition of adjuvants, including dietary rice bran, to L. acidophilus vaccine strains improves their immunogenicity against HIV MPER. Our results indicate that anti-MPER IgG and IgA levels, as well as the number of anti-MPER antibody secreting cells, are improved with adjuvants, and that T cell help is required for an effective immune response. These results, combined with the many advantages offered by this lactic acid bacteria vaccine system make L. acidophilus an attractive vaccine vector for primate and human trials.